2015
DOI: 10.12706/itea.2015.021
|View full text |Cite
|
Sign up to set email alerts
|

Comportamiento materno y bienestar de la coneja doméstica y silvestre y su camada

Abstract: ResumenEl conejo europeo (Oryctolagus cuniculus), además de tener importancia faunística en el Mediterráneo occidental, es una especie ganadera relevante que es la base de un subsector pecuario industrializado orientado a la producción de carne en varios países, sobre todo europeos, mientras que en algunos países en vías de desarrollo se explota bajo sistemas alternativos orientados a la integración de renta y a la seguridad alimentaria. A la orientación cárnica se suman otras aptitudes productivas heterogénea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…On some visits, we observed full-term aborted fetuses (>9 to 10%, Table 3), parturitions outside the nest, and the birth of weak kits. González-Redondo et al [62] indicated parturitions outside the nest in primiparous does, or kits abandoned in the nest, coinciding with low temperatures. Heat stress (>30 • C) makes kindlings and kit survival difficult [8].…”
Section: Other Reproductive Disordersmentioning
confidence: 99%
“…On some visits, we observed full-term aborted fetuses (>9 to 10%, Table 3), parturitions outside the nest, and the birth of weak kits. González-Redondo et al [62] indicated parturitions outside the nest in primiparous does, or kits abandoned in the nest, coinciding with low temperatures. Heat stress (>30 • C) makes kindlings and kit survival difficult [8].…”
Section: Other Reproductive Disordersmentioning
confidence: 99%
“…Rabbit domestication is very recent and there have not been many changes as compared to the wild rabbit, so the behaviour of domestic rabbit is still very similar to wild rabbit, and the biological needs are the same so, under commercial conditions, where specific behaviours or social relationships are impaired, there could arise a welfare problem [6]. Rabbits are social and gregarious animals, and, in wild conditions, they live in groups with more females than bucks (1-4 males and 1-9 females), except around giving birth, when they separate from the rest of the group: the dominant doe uses the common burrow and the rest of the females have to build their nest in different places [7] by mixing their own hair with grass or any other material they can find. The rabbits spend much time resting with conspecifics and in close contact, and fights are produced mainly by hierarchies [8].…”
Section: Animal Welfare In Farmed Animals Including Rabbitsmentioning
confidence: 99%
“…Esto ocurre especialmente en la especie cunícola, para la que "intrínsecamente se relaciona el estar en una jaula con falta de bienestar", como han señalado algunos expertos. En efecto, las jaulas individuales de alambre galvanizado constituyen el alojamiento habitual de la coneja y su camada hasta el destete, tanto en la producción de carne en granjas intensivas como en la mayoría de los núcleos de autoconsumo o en cunicultura alternativa (González-Redondo et al, 2015). Aunque no se han encontrado indicadores de graves problemas de bienestar de los animales, este modelo de producción ha sido cuestionado porque la estancia en la jaula individual limita los comportamientos de locomoción y de contacto social reconocidos en los conejos silvestres, y habitualmente se hace la comparación directa entre ambos grupos, como si la adaptación y la habituación de los animales a su entorno consecuentes a la domesticación no hubieran existido, lo cual es erróneo (Carneiro et al, 2014).…”
Section: Introductionunclassified